If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 7) = 3(x + 6) Reorder the terms: 2(7 + x) = 3(x + 6) (7 * 2 + x * 2) = 3(x + 6) (14 + 2x) = 3(x + 6) Reorder the terms: 14 + 2x = 3(6 + x) 14 + 2x = (6 * 3 + x * 3) 14 + 2x = (18 + 3x) Solving 14 + 2x = 18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 14 + 2x + -3x = 18 + 3x + -3x Combine like terms: 2x + -3x = -1x 14 + -1x = 18 + 3x + -3x Combine like terms: 3x + -3x = 0 14 + -1x = 18 + 0 14 + -1x = 18 Add '-14' to each side of the equation. 14 + -14 + -1x = 18 + -14 Combine like terms: 14 + -14 = 0 0 + -1x = 18 + -14 -1x = 18 + -14 Combine like terms: 18 + -14 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| 13x+70=24 | | 200(2)-15=y | | 4x+3x-x-8-6+4=32 | | -4(5x-3)+7x=2x-4 | | 6(f+5)-8=2f | | 19u-18u=5 | | 4y-30=y+8+2y-3 | | 200(1)-15=y | | .9x-4.9=.5 | | 5*3v-8=-10 | | -0.25(q-1)+0.5=0.75 | | 200m-75m+57900=61500-175m | | 9x+5(x-2)=2(x-3) | | X^2-2px+9=0 | | [(x)(x)]-7x=44 | | 36-9x=19+8x | | 6p-7=-5p+12 | | 200(1)+15=y | | 4x-2x+15-10-6=19 | | 5y-3=2y-15 | | 200(0)+15=y | | 6-9x=6x-10x+1 | | C=3(a+2b) | | -14=8+h | | 3x+2x-18+13=35 | | 9(3m+4)-7m=-4 | | 200(0)-15=y | | 15q-3[4q-6]=3q+9-9q | | 5x+4=26+46 | | 0.3(3x+0.5)= | | -2(5x+2)=-3x+7 | | 12=6ax-4xb |